CLINICOPATHOLOGICAL CHARACTERIZATIONS IN SELECT FOOD ANIMALS IN NORTHERN SAMAR - Camer, Gerry A.; Carpio, Joey Marvin C.; Ocaña, Dina J.; Doncillo, Junry S.; Paredes, Jennylyn T.; Orejudos, Allan R.; Gajutos, Aurelia B.; Amit, Ronaldo A.; Masangkay, Joseph S. (Journal of Agriculture and Technology Management; Vol 21 No 1 (2018): Journal of Agriculture and Technology Management (JATM) Volume 21 January - June 2018 Issue, 2018)
Food-borne zoonoses may occur with ingestion or contact of diseased organs/tissues of food animals slaughtered for public consumption. Food animals include cattle, carabaos, sheep, goats, pigs, and poultry. In this study, the gross and histological features of the lungs, liver, connective and meningeal tissue of pigs and carabaos regarded as food animals were examined. Following gross observations of clinically suspected animals, the muscle, lungs, liver, knee joints and meninges were fixed at 10% buffered formaldehyde and processed for histopathology using paraffin method. Gross examination in a pig showed suppurative changes in the knee joints and brain meninges while congestions were grossly discerned in the lung samples of three sampled carabaos. Histopathology of the lung sections showed alveolar thickening, abundance of red blood cells and inflammatory cells in the alveolar parenchyma. Suppurative arthritis and meningitis were observed and Streptococcus spp. from the knee joints, lymph nodes and liver was isolated from one pig. Further studies involving cultural and law-adherence of slaughtering practices as well as examinations of variety of lesions affecting food animals, which are vital in developing recommendations for thorough meat inspection procedures that will be beneficial to food safety in the region are suggested.